Influence of properties of superheavy nuclei on their α decays; Acta Physica Polonica B; Vol. 48, iss. 3 - Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich; Bezbakh A. N. Anna Nikolaevna; Dzholos R. V. Rostislav Vladimirovich; Malov L. A. Leonard Aleksandrovich; Wang K.; Zhou S. G.; Lenske H. Horst (2017, 2017)
Title screen